Nutritional status and key factors among vagrants at Government Shelter Home Dhaka, Bangladesh - Islam, Mohammad Shahidul; Sarker, Nasir Uddin; Huda, A. F. M. Shahedul; Khatun, Taslima; Shil, Ripon Chandra (International Journal Of Community Medicine And Public Health, 2023)
Background: Nutritional status and others related determinants among vagrants are important issues even in developing countries like Bangladesh. Exploring the current situation it terms of magnitude of people would be a good resource for the policy makers in considering the malnutrition, health care and other supports for the shelter less population. Methods: A cross sectional descriptive study was done. A total of 106 vagabonds form government shelter home were included. The nutritional statuses of the respondents were assessed using measured BMI and dietary pattern was assessed by the 24-hour recall method. The data were processed to undergo statistical analysis using SPSS 23 windows program. Results: The overall mean age of of the respondents 35.3±9.86 years and 42 (39.7%) were in 18-20 years age group and 62% were female. About 62% were correctly married and 22% were single life lead. Less than half (47.1%) of the respondents non-educated, on the other hand 40(37.7%) of the respondents were primary level educated. 22.6% vagrants were abandoned by their family due to certain problems. Association of age group with BMI most respondents were in underweight that gain highly significance where (p=0.0001), there had no association was found between educational status and BMI except non-educated (p=0.025). Most respondents were significant Hand washing before eating, daily bath taken and Suffering from disease Last 1 month with nutritional status where (p=0.020), (p=0.010) and (p=0.0001). Conclusions: Special attention to be given for improving vagabonds care, Attention to improve service quality with special attention to identified areas (balanced diet, treatment etc).